Exposure to Cigarette Smoke Augments Post-ischemic Brain Injury and Inflammation via Mobilization of Neutrophils and Monocytes - Li, Handong; Li, Xiuping; Gao, Siman; Wang, Dan; Gao, Xiaolin; Li, Yujing; Wang, Xuejiao; Cui, Zhigang; Ma, Hongshan; Liu, Qiang; Li, Minshu (Frontiers in Immunology, 2019)
Cigarette smoke is a major preventable risk factor of ischemic stroke. Cigarette smoke induces a significant increase of circulating leukocytes, however, it remains unclear to what extent and by what mechanisms smoke priming influences stroke severity. Here we report that exposure to cigarette smoke exacerbated ischemic brain injury in mice subjected to transient middle cerebral artery occlusion (MCAO). The augmentation of neurodeficits and brain infarction was accompanied by increased production of pro-inflammatory factors and brain infiltration of neutrophils and monocytes. Prior to brain ischemia, exposure to cigarette smoke induced mobilization of peripheral neutrophils and monocytes. Further, the detrimental effects of smoke priming on ischemic brain injury was abolished either by pharmacological inhibition of the recruitment of neutrophils and monocytes, or by blockade of NLRP3 inflammasome, an effector protein of neutrophils and monocytes. Our findings suggest that cigarette smoke-induced mobilization of peripheral neutrophils and monocytes augments ischemic brain injury.